Inheritance, war and antiquarianism: Sir Alan Stewart of Darnley, 2nd seigneur d’Aubigny et de Concressault 1429-37 - Bonner, Elizabeth (Proceedings of the Society of Antiquaries of Scotland, 2014)
This article concerns the establishment in France of the Lennox-Stuarts/Stewarts of Darnley at the height of the Hundred Years War in the 1420s. In time, they were to become possibly the single most important family involved in the politics and diplomacy of the monarchies and government in the kingdoms of Scotland, France and England during the entire 15th and 16th centuries. This research also concerns a re-evaluation of the works of those 18th- and 19th-century antiquarians who have been the principal authors of this family's Histories, by verifying their interpretations of sources, in particular their manuscript sources in the archives and libraries of all three ancient kingdoms. This is in line with recent reviews of the works of antiquarians of all eras; but the works of the 18th-century antiquarians have been of particular interest. Thus, the history of this family has relied, up until now, entirely on the works of antiquarians which, due to general pejorative views of their publications, have suffered a seeming distrust by modern professional historians. Finally, recent research into the private Stuart archives at the Chateau de La Verrerie demonstrates the rationale and legal mechanisms by which Charles VII intervened in 1437 regarding the inheritance of Sir Alan Stewart of Darnley's seigneuries d'Aubigny et Concressault by his brother John. This document is important, as it set a precedence for later legal inheritance and transfer of the titles of the seigneuries in the family, and ultimately to transferring the lands and title to the Scottish Lennox-Stuarts/Stewarts and their descendents in the 16th century.